Quality of Life Development for the Elderly With Local Leader Participation in Huai Phueng District, Kalasin Province - Sumeto (Wareebor), Phrapalad Supot; Sawatta, Sutipong; Promgun, Suraphon (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were: 1) to study the condition of developing the quality-of-life of the elderly through the participation of local leaders in Huai Phueng District, Kalasin Province; 2) to compare the quality-of-life development for the elderly through the participation of local leaders in Huai Phueng District, Kalasin Province; and 3) to study the approaches for improving the quality-of-life of the elderly through the participation of local leaders in Huai Phueng District, Kalasin Province by applying the Four Iddhipda Dhamma. The sample group included 267 local leaders in Huai Phueng District and 12 key informants. The tools used were a questionnaire and an interview form. Data were analyzed using social science software packages and contextual content analysis. The research results were as follows: 1) The level of quality-of-life development for the elderly through the participation of local leaders in Huai Phueng District in four aspects: (1) physical aspect; (2) mental aspect, (3) social relationship aspect; (4) environment aspect was statistically rated at a high level. In aspect consideration, the aspect with the highest mean was the physical aspect ( = 4.04), followed by the social relationship aspect ( = 4.00), environment aspect ( = 3.93) and mental aspect ( = 3.87). 2) The comparative results of the quality-of-life development for the elderly through the participation of local leaders in Huai Phueng District, Kalasin Province indicated that people with differences in ages, education levels, occupations, and average monthly incomes differently participated in improving the quality-of-life of the elderly with the statistical significance level of 0.05. People of different genders indifferently participated in improving the quality-of-life of the elderly. 3) Suggestions were that the focus should be on understanding the members and the intentions of the club and its roles. News and knowledge about the elderly should be followed. The local leaders should seek sources of support for knowledge and people with specific knowledge or wisdom in various fields in the community organize activities regularly andThey should find a network with individuals and organizations locally and outside the area.